ANALISIS KESUKSESAN WEBSITE BKPSDMD KOTA JAMBI MENGGUNAKAN MODEL DELONE DAN MCLEAN - Pratama, Rizky (ZONAsi: Jurnal Sistem Informasi, 2024)
In this modern era, we can see changes in activities that were previously carried out manually, now being changed by digitalization. so that work becomes easier and more efficient. Currently, digitalization is developing rapidly and is widely used, namely information systems that make it easier to access online information which can be done anywhere via the internet. An information system is a system within an organization that meets daily transaction processing needs, supports organizational functions in the organization's strategic activities, and provides reports required by certain external parties. One form of information system that has been implemented in Regional Apparatus Organizations is the Jambi City BKPSDMD website which has been used by Jambi City BKPSDMD employees, government employees outside the Jambi City BKPSDMD, and the public who need government information. The Jambi City BKPSDMD website has never had any research regarding the success of its website, so the quality of its website's success is not yet known. The success of the website will be measured by the effectiveness, benefits and user satisfaction after using the Jambi City BKPSDMD website. It is hoped that the results of this research evaluation can become a guide in improving and optimizing the performance of the Jambi City BKPSDMD website. The questionnaire assessment from the results of 100 respondents with 17 indicators stated that the average was close to good and even reached a good level by producing a score of 3.973 rounded to 4, which means that the Jambi City BKPSDMD website was declared good based on the Likert scale assessment of this research through drawing the conclusion that it was very bad (1), not good (2), quite good (3), good (4), and very good (5).